Cost-Minimizing Regulation of Sulfur Emissions: Regional Gains in Electric Power - Gollop, Frank M.; Roberts, Mark J. (The Review of Economics and Statistics, 1985)
Environmental regulations set maximum allowable rates for sulfur dioxide emissions from electric utilities. By ignoring firm differences in marginal abatement costs and preventing emissions trading, these standards do not minimize the cost of reducing einissions. This paper estimates marginal abatement cost functions for 56 utilities for 1973-79. Marginal costs vary substantially across firms due to differences in the price of low and high sulfur fuels and the intensity of regulation. The potential savings from a cost minimizing reallocation of abatement resources are estimated for five regions. Current expenditures are found to be 47% higher than cost minimizing levels. I MPLEMENTATION of the 1970 Clean Air Act Amendments relies extensively on technology-based emission standards. Economists long have recognized that these standards can result in an inefficient allocation of pollution control resources.' Engineering-based restrictions ignore or oversimplify differences in abatement costs among polluters. Limited empirical research suggests that current standards result in substantially higher costs, as much as ten times higher, than a cost-minimizing regulatory scheme.2 These studies, however, are based on engineering estimates of marginal abatement costs. The models often assume that all polluters adopt control technologies that are required only for new plants and that have been largely unadopted by polluting firms.3 The impact of changing factor prices on marginal abatement costs typically is ignored. The difficulty is that the resulting estimates of the cost of regulation neither adequately reflect the range of control options available to polluters nor take into account how polluters actually have responded to environmen-